2019
DOI: 10.1136/bcr-2018-225385
|View full text |Cite
|
Sign up to set email alerts
|

Beware of bone pain with bisphosphonates

Abstract: A 71-year-old woman who had been taking ibandronate for 10 years presented to an Endocrinology Department with persistent mid-thigh pain. Pelvic X-ray showed bilateral femoral cortical expansion, indicating impending atypical femoral fractures (AFFs). AFFs have been linked to long-term bisphosphonate therapy and have morbidity and mortality similar to that of hip fractures. Such fractures can be averted by regular reviews of bisphosphonate therapy and vigilance for prodromal symptoms. This patient’s bisphospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
(19 reference statements)
0
7
0
1
Order By: Relevance
“…6,7) However, anecdotal studies showed improvement without surgery using TPTD as anabolic therapy. 9) TPTD, a PTH(1-34) fragment, is another option for the treatment of incomplete AFFs. There is low-quality evidence that TPTD increases bone healing in patients with BP-related AFFs by enhancing bone turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7) However, anecdotal studies showed improvement without surgery using TPTD as anabolic therapy. 9) TPTD, a PTH(1-34) fragment, is another option for the treatment of incomplete AFFs. There is low-quality evidence that TPTD increases bone healing in patients with BP-related AFFs by enhancing bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…6 , 7 ) However, anecdotal studies showed improvement without surgery using TPTD as anabolic therapy. 9 )…”
Section: Discussionmentioning
confidence: 99%
“…For decades, the demand for artificial joints has been growing dramatically [ 1 , 2 , 3 ], while the research and development of new artificial bone joints has attracted extensive attention [ 4 , 5 , 6 ]. However, secondary injury after implantation, which is mainly caused by postoperative infection and wear of materials [ 7 ], is a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…Bone fractures are the leading cause of hospitalisations worldwide [1], with approximately 2.8 million bone repair cases performed annually [2]. The bone repair market was recorded at $53 billion globally in 2018, with the expectation of increasing to $75 billion by 2023 [3].…”
Section: Introductionmentioning
confidence: 99%